2022
DOI: 10.1101/2022.12.18.22283593
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of bivalent Omicron BA.1 booster vaccination after different priming regimens in healthcare workers (SWITCH ON): a randomized controlled trial

Abstract: Background Bivalent mRNA-based COVID-19 vaccines encoding the ancestral and Omicron spike protein were developed as a countermeasure against antigenically distinct SARS-CoV-2 variants. We compared the (variant-specific) immunogenicity and reactogenicity of mRNA-based bivalent Omicron BA.1 vaccines in individuals who were primed with adenovirus- or mRNA-based vaccines. Methods In this open-label, multicenter, randomized, controlled trial, healthcare workers primed with Ad26.COV2.S or mRNA-based vaccines were bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…However, the effect of bivalent vaccines on T cell immunity remains less understood and further studies are still required. A recent study by Tan et al has shown that bivalent booster vaccination leads to a robust recall of memory T cell responses within the first 7 days after boost, that exhibit cross-reactivity against Omicron BA.1 and BA.5 variants regardless of the priming regime administered (234).…”
Section: Hybrid Immunity Against Sars-cov-2mentioning
confidence: 99%
“…However, the effect of bivalent vaccines on T cell immunity remains less understood and further studies are still required. A recent study by Tan et al has shown that bivalent booster vaccination leads to a robust recall of memory T cell responses within the first 7 days after boost, that exhibit cross-reactivity against Omicron BA.1 and BA.5 variants regardless of the priming regime administered (234).…”
Section: Hybrid Immunity Against Sars-cov-2mentioning
confidence: 99%